The effect of anisotropy of elastic properties of GFRP reinforcement on strength of compressed concrete structural elements - Mikhail G. Plyusnin (Vestnik MGSU, 2019)
Introduction. Despite the growing interest to the use of GFRP reinforcement in various concrete structures, its use in the concrete compressed zone is not investigated sufficiently. The use of GFRP reinforcement in compressed concrete elements is limited by a combination of low value of its modulus of elasticity and small ultimate deformation of concrete during compression. A number of researchers suggest solving this problem by means of increase the ultimate concrete deformation due to lateral reinforcement. However, unlike steel reinforcement, the elastic properties of composite reinforcement depend on the stress direction, which is due to the significant difference between the moduli of elasticity of the fibre glass and the binder. Consequently, the stress-deformation state of compressed concrete elements with longitudinal GFRP reinforcement and close-set lateral reinforcement will differ from the stress-deformation state of steel-reinforced concrete elements.